Jamshed The Divine King In ancient Iranian mythology - Abood Sammar, Saad (Journal of College of Education, 2020)
This study sheds light on one of the legendary kings in the ancient Iranian Mithi history, as Jamshid is considered the most important king of the legendary Pisidian era, and that the details of his life and kingdom, and the work that he immortalized in its memory, became a common article in the ancient Iranian-Indian mythology. The research will touch on his personality, his kingdom, his accomplishments, his works, the story of the snow flood that was its hero, and the savior of mankind in it, and how the gods weakened and abandoned him, lost his divine conciliation, and eventually led to the end of his kingdom, and then his death.